Slaying axion-like particles via gravitational waves and primordial black holes from supercooled phase transition - Angela Conaci; Luigi Delle Rose; P. S. Bhupal Dev; Anish Ghoshal (Journal of High Energy Physics)
Abstract We study the formation of primordial black holes (PBHs) from density fluctuations due to supercooled phase transitions (PTs) triggered in an axion-like particle (ALP) model. We find that the mass of the PBHs is inversely correlated with the ALP decay constant f a . For instance, for f a varying from O $$ \mathcal{O} $$ (100 MeV) to O $$ \mathcal{O} $$ (1012 GeV), the PBH mass varies between (103 − 10 −24)M ⊙. We then identify the ALP parameter space where the PBH can account for the entire (or partial) dark matter fraction of the Universe, in a single (multi-component) dark matter scenario, with the ALP being the other dark matter candidate. The PBH parameter space ruled out by current cosmological and microlensing observations can thus be directly mapped onto the ALP parameter space, thus providing new bounds on ALPs, complementary to the laboratory and astrophysical ALP constraints. Similarly, depending on the ALP couplings to other Standard Model particles, the ALP constraints on f a can be translated into a lower bound on the PBH mass scale. Moreover, the supercooled PT leads to a potentially observable stochastic gravitational wave (GW) signal at future GW observatories, such as aLIGO, LISA and ET, that acts as another complementary probe of the ALPs, as well as of the PBH dark matter. Finally, we show that the recent NANOGrav signal of stochastic GW in the nHz frequency range can be explained in our model with f a ≃ (0.1 GeV − 1 TeV).